Treatment with Herbal Formula Extract in the hSOD1G93A Mouse Model Attenuates Muscle and Spinal Cord Dysfunction via Anti-Inflammation - Yang, Eun Jin; Lee, Sun Hwa; Cai, Mudan (Mediators of Inflammation, 2022)
Amyotrophic lateral sclerosis (ALS), a multicomplex neurodegenerative disease, has multiple underlying pathological factors and can induce other neuromuscular diseases, leading to muscle atrophy and respiratory failure. Currently, there is no effective drug for treating patients with ALS. Herbal medicine, used to treat various diseases, has multitarget effects and does not usually induce side effects. Each bioactive component in such herbal combinations can exert a mechanism of action to increase therapeutic efficacy. Herein, we investigated the efficacy of an herbal formula, comprising Achyranthes bidentata Blume, Eucommia ulmoides Oliver, and Paeonia lactiflora Pallas, in suppressing the pathological mechanism of ALS in male hSOD1G93A mice. Herbal formula extract (HFE) (1 mg/g) were orally administered once daily for six weeks, starting at eight weeks of age, in hSOD1G93A transgenic mice. To evaluate the effects of HFE, we performed footprint behavioral tests, western blotting, and immunohistochemistry to detect protein expression and quantitative PCR to detect mRNA levels in the muscles and spinal cord of hSOD1G93A mice. HFE-treated hSOD1G93A mice showed increased anti-inflammation, antioxidation, and regulation of autophagy in the muscles and spinal cord. Thus, HEF can be therapeutic candidates for inhibiting disease progression in patients with ALS. This study has some limitations. Although this experiment was performed only in male hSOD1G93A mice, studies that investigate the efficacy of HEF in various ALS models including female mice, such as mice modeling TAR DNA-binding protein 43 (TDP43) and ORF 72 on chromosome 9 (C9orf72) ALS, are required before it can be established that HEF are therapeutic candidates for patients with ALS.